Dose Response of MTLN3 Cells to Serial Dilutions of Arsenic Trioxide and Ionizing Radiation - Waseem Khan Raja; Jahangir Satti; Gang Liu; James Castracane (SAGE Publishing, 2013)
MTLn3 cells derived from mouse mammary epithelium are known to be highly malignant and are resistant to both radio- and chemo-therapy. We exposed MTLn3 cells to various doses of inorganic Arsenic trioxide (As 2 O 3 ) in combination with ionizing radiation. Cells were treated with a series of As 2 O 3 concentrations ranging from 20 μM to 1.22 nM for 8 hour, 24 hour and 48 hour periods. Post-treated cell proliferation was quantified by measuring mitochondrial activity and DNA analysis. Cells exposed to radiation and As 2 O 3 at concentration greater than 1.25 μM showed apoptosis and radiations alone treated cells were statistically not different from the control. Hormesis was observed for As 2 O 3 concentrations in the range of 0.078 μM to 0.625 μM while the combined chemo and radiation treatments of the cells did not affect the hormetic effect. We have demonstrated that As 2 O 3 (in the presence and absence of ionizing radiation) in specific low concentrations induced apoptosis in the otherwise chemoresistant cancer cells. This low concentration-mediated cell death is immediately followed by a surge in cell survival. Low dosing dosimetry is highly desirable in metronomic therapy however, it has a narrow window since necrosis, hormesis, apoptosis and other dose-dependent biological processes take place in this region. Further quantifiable dosimetry is highly desired for routine clinical practice.